Highly specific and sensitive non-radioactive molecular identification of Phytophthora cinnamomi - Coelho, A. C. (2012)
In response to the need for a faster, more reliable method for identifying Phytophthora cinnamomi in cork oak soils in Portugal, a simple, fast, sensitive molecular identification method is described. It is based on a colorimetric assay which involves an oligonucleotide capture probe covalently immobilised on microtitration wells, a multi-biotinylated oligonucleotide detection probe and the PCR-amplified target DNA. The target DNA is a 349 bp DNA fragment partially covering the 3'-translated and 3'- untranslated regions of the cinnamomin gene. When the specificity of the PCR reaction was evaluated in vitro using isolates of P. cinnamomi and eight other Phytophthora species, including the related P. cambivora, it was specific to P. cinnamomi. When 30 isolates of P. cinnamomi from oak roots in southern Portugal were assayed, 26 gave a strong positive response. The assay has a sensitivity of about 2±5 genome equivalents of P. cinnamomi. The reason for the negative response of four isolates remains unclear.